2015
DOI: 10.1016/j.dnarep.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction between SLX4 (FANCP) and XPF (FANCQ) proteins and biological consequences of interaction-defective missense mutations

Abstract: SLX4 (FANCP) and XPF (FANCQ) proteins interact with each other and play a vital role in the Fanconi anemia (FA) DNA repair pathway. We have identified a SLX4 region and several amino acid residues that are responsible for this interaction. The study has revealed that the global minor allele, SLX4Y546C, is defective in this interaction and cannot complement Fancp knockout mouse cells in mitomycin C-induced cytotoxicity or chromosomal aberrations. These results highly suggest this allele, as well as SLX4L530Q, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 25 publications
(38 reference statements)
2
23
0
Order By: Relevance
“…We previously showed that the xlXPF-hsERCC1 complex (referred to as XPF-ERCC1 from here on) supports ICL repair in Xenopus egg extracts (Klein Douwel et al, 2014). Expression levels of all mutant complexes were similar to wild-type levels except for the XPF L219P -ERCC1 (XE L219P ) complex that was previously reported to be unstable Hashimoto et al, 2015). To examine the function of leucine 219, we instead mutated it to an arginine and found that XE L219R was expressed at normal levels.…”
Section: Xpf Mutants Form Functional Complexes With Ercc1mentioning
confidence: 79%
“…We previously showed that the xlXPF-hsERCC1 complex (referred to as XPF-ERCC1 from here on) supports ICL repair in Xenopus egg extracts (Klein Douwel et al, 2014). Expression levels of all mutant complexes were similar to wild-type levels except for the XPF L219P -ERCC1 (XE L219P ) complex that was previously reported to be unstable Hashimoto et al, 2015). To examine the function of leucine 219, we instead mutated it to an arginine and found that XE L219R was expressed at normal levels.…”
Section: Xpf Mutants Form Functional Complexes With Ercc1mentioning
confidence: 79%
“…We generated a series of SLX4 deletion mutants based on SLX4’s known interaction domain or functional motif. We found that deletion of the MEI9 XPF interaction like region (MLR) of SLX4 (residues 409–555), which is considered the binding site for XPF–ERCC1 (84,85), abolished its interaction with SLX4IP (Figure 3B). We generated further small-deletion mutants in the MLR domain and found that deletion of residues 501–555 of SLX4 not only abolished its interaction with XPF but also impaired its interaction with SLX4IP (Supplemental Figure S3A).…”
Section: Resultsmentioning
confidence: 98%
“…SLX4 and XPF–ERCC1 are the major SLX4IP-interacting proteins, with or without MMC-based treatment (Figure 3A). Studies have demonstrated that SLX4 coordinates with XPF–ERCC1 and participates in the unhooking of ICLs during the repair process (31,43,67,84). The binding of SLX4IP to both SLX4 and XPF–ERCC1 inspired us to further investigate whether SLX4IP plays a role in regulating SLX4–XPF–ERCC1 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The second allele of XPF presented a novel splice site mutation (c.793-2A>G) which produced a premature termination of translation (p.Thr265Valfs*13), hence originating a null allele as happened with the previously reported FA XPF variants [35]. Contrary to Hashimoto group, who found the XPF-R589W mutation was abruptly affecting XPF structure and its SLX4 binding [45]. Popp and colleagues detected a residual proportion of XPF-R589W escaping from protein misfolding, able to reach the chromatin [43] as happened with the reported FA XPF variants.…”
Section: Resultsmentioning
confidence: 99%